Comparative study of energy storage technologies for oil platforms with distributed Microgeneration - Costa, Henrique; Barcelos, Silvangela; Santos Jr, Bartolomeu; Santos, Walbermark (Latin American Journal of Energy Research, 2024)
On oil extraction platforms, several systems work together, ensuring the proper functioning of the drilling, production, storage, and oil transfer processes to guarantee the fulfillment of critical loads, even in cases of failure of the oil extraction systems. Generation cannot be stopped. This service can be provided through an energy storage system in a battery bank associated with the generation mix. The result of this study presents a comparative analysis of the technologies on the market, which can be considered eligible to be associated with the generation mix of a Fixed-type platform. The Homer software will be used to measure the results of this comparative analysis.